Rapid and robust restoration of breathing long after spinal cord injury. Issue 1 (December 2018) - Warren, Philippa; Steiger, Stephanie; Dick, Thomas; MacFarlane, Peter; Alilain, Warren; Silver, Jerry
Abstract There exists an abundance of barriers that hinder functional recovery following spinal cord injury, especially at chronic stages. Here, we examine the rescue of breathing up to 1.5 years following cervical hemisection in the rat. In spite of complete hemidiaphragm paralysis, a single injection of chondroitinase ABC in the phrenic motor pool restored robust and persistent diaphragm function while improving neuromuscular junction anatomy. This treatment strategy was more effective when applied chronically than when assessed acutely after injury. The addition of intermittent hypoxia conditioning further strengthened the ventilatory response. However, in a sub-population of animals, this combination treatment caused excess serotonergic (5HT) axon sprouting leading to aberrant tonic activity in the diaphragm that could be mitigated via 5HT2 receptor blockade. Through unmasking of the continuing neuroplasticity that develops after injury, our treatment strategy ensured rapid and robust patterned respiratory recovery after a near lifetime of paralysis. Respiratory failure is one of the leading causes of death following spinal cord injury and it is unclear if normal respiratory motor activity can be recovered after chronic injury-induced paralysis. Here, authors show that treatment with chondroitinase ABC induces robust rescue of breathing up to 1.5 years following complete hemidiaphragm paralysis.